2016
DOI: 10.1007/s00167-016-4190-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the patella height on the strain pattern of the medial patellofemoral ligament after reconstruction: a computer model-based study

Abstract: When reconstructed in the radiological femoral insertion point, MPFL strain patterns were only slightly affected by different patella heights (IS 0.74-1.5) suggesting that MPFL reconstruction could be safely performed using the radiological insertion. However, in case of a patella alta (IS 1.5), a slightly more proximal femoral insertion is beneficial for the biomechanical behaviour of the reconstructed MPFL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 42 publications
1
35
0
2
Order By: Relevance
“…In order to account for physiological force exertion, large muscles were divided into several force elements and wrapping as well as deflection phenomena were considered by deploying segment‐fixed via‐points. In particular, the deflection of the quadriceps tendon by the trochlear groove was realized by identifying the via‐points by means of a previously presented model of the patellofemoral joint . Passive forces due to capsular tissue have been neglected.…”
Section: Methodsmentioning
confidence: 99%
“…In order to account for physiological force exertion, large muscles were divided into several force elements and wrapping as well as deflection phenomena were considered by deploying segment‐fixed via‐points. In particular, the deflection of the quadriceps tendon by the trochlear groove was realized by identifying the via‐points by means of a previously presented model of the patellofemoral joint . Passive forces due to capsular tissue have been neglected.…”
Section: Methodsmentioning
confidence: 99%
“…Based on cadaveric studies applying an isolated lateral force to the patella, the MPFL provides more than 50% of the passive resistance to lateral translation [7, 8]. A cadaveric study and computational simulation study focused on the path length of the normal MPFL as a function of the flexion angle indicated that the length tends to decrease beyond 60° of knee flexion [9, 10], although another in vitro study indicated the MPFL length tends to increase beyond 60° of knee flexion [5]. Several in vitro simulation studies have evaluated the influence of the native MPFL on patellar tracking.…”
Section: Mpfl Reconstructionmentioning
confidence: 99%
“…The Schöttle point has been used as a reference standard to assess the accuracy of MPFL femoral tunnel placement after reconstructive surgery. 2 , 11 , 18 , 22 , 28 , 46 …”
mentioning
confidence: 99%